Pharmacokinetics and Enterohepatic Circulation of 2-(Quinoline-8-carboxamido)benzoic Acid (2-QBA) in Mice - Ji-Hyeon Jeon; So-Yeon Jeon; Yeon-Ju Baek; Chan-E Park; Min-Koo Choi; Young Taek Han; Im-Sook Song (MDPI AG, 2024)
The quinoline alkaloid 2-(quinoline-8-carboxamido)benzoic acid (2-QBA), which is isolated from Aspergillus sp. SCSIO06786, a deep sea-derived fungus, has been suggested as a therapeutic candidate for the treatment of Parkinson's disease. We developed an analytical method for 2-QBA using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) in mouse plasma, in which a protein precipitation method for the sample preparation of 2-QBA in mouse plasma was used due to its simplicity and good extraction recovery rates (80.49-97.56%). The linearity of the calibration standard sample, inter- and intraday precision and accuracy, and stability of three quality control samples were suitable based on the assessment criteria and the lower limit of quantification (LLOQ) of the 2-QBA was 1 ng/mL. A pharmacokinetic study of 2-QBA was performed in mice divided into oral (2.0, 5.0, and 15 mg/kg) and intravenous (0.5 and 1.0 mg/kg) administration groups. The absolute oral bioavailability (BA) range of 2-QBA was calculated as 68.3-83.7%. Secondary peaks were observed at approximately 4-8 h after the oral administration of 2-QBA at all doses. The elimination half-life of the orally administered 2-QBA was significantly longer than that of the intravenous 2-QBA. In addition, glucuronide metabolites of 2-QBA were identified. They were transformed into 2-QBA using the β-glucuronidase treatment. Furthermore, the 2-QBA was readily absorbed from the jejunum to lower ileum. Taken together, the secondary peaks could be explained by the enterohepatic circulation of 2-QBA. In conclusion, the reabsorption of orally administered 2-QBA could contribute to the high oral BA of 2-QBA and could be beneficial for the efficacy of 2-QBA. Moreover, the simple and validated analytical method for 2-QBA using LC-MS/MS was applied to the pharmacokinetic study and BA assessments of 2-QBA in mice and would be helpful for subsequent pharmacokinetic studies, as well as for evaluations of the toxicokinetics and pharmacokinetic-pharmacodynamic correlation of 2-QBA to assess its potential as a drug.